Neck/shoulder pain, habitual spinal posture and computer use in adolescents: the importance of gender - Straker, Leon; Smith, Anne; Bear, N.; O'Sullivan, Peter; de Klerk, N. (Taylor & Francis Ltd., 2011)
Neck/shoulder pain is a common complaint, with evidence suggesting rates in adolescence have increased in line with increased computer use. The study aimed to examine the influence of gender on relationships between computer use, habitual posture and neck/shoulder pain. Adolescents (n = 1483) participating in the 14 year follow-up of the Raine Study cohort were surveyed for computer use, habitual sitting posture and neck/shoulder pain. Females used computers less than males (52% vs. 45% used for up to 7 h per week). Females sat much more upright than males with greater anterior pelvic tilt (9.48 vs. 0.48). Females reported a higher 1 month prevalence of neck/ shoulder pain (34.7%) than males (23.1%). A multivariate model showed neck/shoulder pain risk was increased in females (OR 2.61, 95% CI 1.70–4.00) and with computer use (OR 1.19, CI 1.01–1.40). Computer use is related to neck/shoulder pain and posture in adolescents but this relationship is different in boys and girls.